Impact Of Organizational Climate On Employees’ Organizational Commitment In Nepal: A Case Study Of Nepal Bank LTD - Poudel, Surya Prasad; Aryal, Kul Prasad (Journal of Islamic Economics Perspectives, 2024)
This paper aims to examine the impact of dimensions of organizational climate on organizational commitment on bank employees of the Nepal Bank Ltd. The Nepal Bank Ltd was selected under purposive sampling method. Structural 5 points Likert Scale organizational climate and organizational commitment questionnaires were designed and distributed to 157 offiicers and table work employees selected under systematic random sampling method out of 326 employees. Only 114 respondents have filled up and returned questionnaire forms within the given period. The statistical tools correlation and simple linear regression were deployed for analysis purpose by the helps of SPSS 18th crack version. The analysis has shown significant positive correlation of the dimensions of organizational climate and dimensions of organizational commitment with correlation values from 0.432 to 0.605. Likewise the impact of dimensions of organizational climate proportionate have changed in organizational climate by 52.9 percent. The management and policy makers of the bank should enhance organizational commitment through improvement of organizational climate of the bank.